Let's hear it from her lived experiences of the other woman. - Abanes, Merry Rose B.; Cabiling, Maria Carmina P.; Nonay, Mary Grace A.; Rayos, Janna Joy E. (Merry Rose B. Abanes, 2013)
Women involved in extra dyadic affairs have been stereotyped as "home wreckers" and are seen as women whose only reason is for financial needs. Other studies on the other hand, limit their findings to how men view their affairs, overlooking the perspective of the 'Other woman'. This paper sheds light on what influences or pushes the "Other woman" to be involved in an extramarital affair and at the same time explore the inside world of 'The Other Woman'. Through in-depth interviews, predominant themes have surfaced as to why these "Other Women" engaged in such "frowned upon" affairs. Societal perception and the quality of the alternative, that is, the men these women are involved with other than their legal partners serve as predominant influences presented in the study reflecting environmental influences affecting their involvement in extramarital affairs as espoused by evolutionary psychology perspective. Majority of them identified themselves as mistresses and engaged for the reasons that tend to lean more on companionship and financial needs. Finding themselves in such a situation, these women manifested certain coping strategies found to be dependent mainly on their unique situation. Lived experiences of 'The Other Women' are not new, but it provides a deeper understanding of their situation, gives a chance at correcting misconceptions and broadens the perspective of Filipinos on relationships and sexuality.